2001
DOI: 10.1007/s004380100569
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in ornamental and common carp strains (Cyprinus carpio L.) as revealed by AFLP analysis and a new set of microsatellite markers

Abstract: Forty-seven new microsatellite markers were generated and applied, together with the AFLP (Amplified Fragment Length Polymorphism) technique using two different enzyme combinations, to the genetic analysis of two carp species, Cyprinus carpio L. and Ctenopharyngodon idella. The extent of polymorphism and the genetic relationships between nine carp populations were studied. The incidence of microsatellites containing CA and CT motifs was estimated to be one every 17.4 and one every 126.3 kb, respectively, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 16 publications
1
30
1
3
Order By: Relevance
“…In addition, the BC 1 analyses indicated that the scale coverage pattern was not correlated with CyHV-3 resistance and therefore, it should be possible to obtain resistant mirror strains using our strategy. Secondly, with respect to genetic variability and inbreeding, the parental stocks of “Y” and “D” strains are kept as closed inbred populations since the 1970s and consequently they present reduced genetic variation and possibly also some degree of inbreeding depression (Moav et al, 1975; Kincaid, 1983; David et al, 2001, 2007). Survival levels after CyHV-3 infection could also be looked at as an example trait from which we can learn on variation among our strains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the BC 1 analyses indicated that the scale coverage pattern was not correlated with CyHV-3 resistance and therefore, it should be possible to obtain resistant mirror strains using our strategy. Secondly, with respect to genetic variability and inbreeding, the parental stocks of “Y” and “D” strains are kept as closed inbred populations since the 1970s and consequently they present reduced genetic variation and possibly also some degree of inbreeding depression (Moav et al, 1975; Kincaid, 1983; David et al, 2001, 2007). Survival levels after CyHV-3 infection could also be looked at as an example trait from which we can learn on variation among our strains.…”
Section: Discussionmentioning
confidence: 99%
“…Locus Koi105‐106 was described in C. carpio by David et al . (). Locus Cca02 was described in C. carpio by Yue et al .…”
Section: Methodsmentioning
confidence: 97%
“…First nine loci listed above were included by Yue, Ho, Orban and Komen () in the list of 21 microsatellite loci recommended for genetic diversity studies of common carp. Primer sequence information was taken from the following sources: for loci MFW4 , MFW7 and MFW26 from Crooijmans, Bierbooms, Komen, Van der Poel and Groenen (), for loci Koi29‐30 , Koi105‐106 and Koi115‐116 from David, Rajasekaran, Fang, Hillel and Lavi (), for loci Cca02 , Cca04 and Cca24 from Yue et al . (), and for locus Cca‐21 from Aliah, Takagi, Dong, Teoh and Taniguchi ().…”
Section: Methodsmentioning
confidence: 99%